Thermodynamic Rarity and the Loss of Mineral Wealth - Antonio Valero; Alicia Valero (Energies, 2015)
The second law of thermodynamics and, specifically, exergy analysis have been traditionally used for the assessment and optimization of energy systems. Nevertheless, as shown in this paper, exergy could also constitute a powerful tool for the evaluation of mineral commodities. That said, new or re-defined exergy-based concepts need to be developed. This paper presents Thanatia as a baseline for evaluating the exergy of any mineral in the crust and opens the door to discuss the “thermodynamic rarity” concept as a basis for exergy analyses for mineral systems. Thermodynamic rarity is understood as the amount of exergy needed to obtain a given mineral from a completely degraded state, denoted as Thanatia. The rarer the mineral, the greater the associated exergy costs. It quantifies value, as it relates to concentration, chemical composition and cohesion, key aspects that determine whether a mine is exploitable. The theory further allows one to quantify the gradual loss of mineral capital on Earth as a consequence of “rarefaction processes” that occur at a mineral’s end-of-life, when a commodity is wasted, and at its beginning-of-life, where mining ore grades decline after extraction.